TEKNIK PENGUMPULAN DATA DAN PENGEMBANGAN INSTRUMEN DALAM PENELITIAN ILMIAH - Apriyudin, Apriyudin; Hayadi, B. Herawan; Haryati, Reti Sri; Nurlina, Nina; Putro, Muhammad Wachid Suryo; Zikriyanto, Wahyu (STAI Darul Qalam Tangerang, 2026)
The quality of scientific research results is highly determined by the accuracy of data collection techniques and the reliability of the instruments used. This study aims to synthesize and comprehensively examine various data collection techniques in quantitative and qualitative approaches, instrument development procedures, and data quality testing mechanisms through validity, reliability, and validity checks of data. The method used in this study is a library research by analyzing 16 scientific documents consisting of methodological textbooks and accredited national journals. The results of the study show that in the quantitative approach, data collection is dominated by the use of structured instruments such as tests and questionnaires that must meet the criteria of content validity, construct, and reliability through Cronbach's Alpha coefficient. Meanwhile, the qualitative approach emphasizes the researcher as a key instrument with in-depth interview, observation, and documentation techniques that are strengthened through triangulation strategies to ensure the credibility of the data. The research findings confirm that the research instrument is not static; Changes in social and cultural contexts require researchers to retest to ensure the accuracy of the data. In addition, in educational research, the analysis of the characteristics of question items such as the level of difficulty and differentiating power is crucial in producing quality evaluation instruments. This study concludes that the integration between relevant data collection techniques and validated instruments is an absolute requirement to produce credible, objective, and academically accountable research findings. This article is expected to be a methodological guide for researchers and education practitioners in compiling effective research instruments.